A CONCEPTUAL FRAMEWORK FOR UNDERSTANDING STRESS, ANXIETY, DEPRESSION, AND BURNOUT AMONG ACADEMIC AND NON-ACADEMIC UNIVERSITY STAFF - Karim, Hazrul Hizam; Yusooff, Fatimah; Jailani, Mohd Azli Md; Abd Hamid, Nur Bakri; Zulkepli, Muhammad Izzul Syahmi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Mental health challenges such as stress, anxiety, depression, and burnout have become pressing concerns for both academic and non-academic staff in higher education institutions, driven by rising workloads, administrative demands, and organisational change. This study aims to develop a comprehensive conceptual framework to explain how job demands contribute to burnout, incorporating three established theories: The Job Demands-Resources (JD-R) model, Conservation of Resources (COR) theory, and Social Support Theory. The framework positions stress, anxiety, and depression as mediating variables that arise from prolonged exposure to excessive job demands, while organisational resources and interventions such as social support, autonomy, and structured wellbeing policies act as moderating factors that can buffer these effects. Through theoretical integration and conceptual synthesis, the study finds that burnout is more likely to occur when psychological distress remains unaddressed due to insufficient workplace support, leading to emotional exhaustion, depersonalisation, and reduced personal accomplishment. The framework highlights the importance of theory-based, context-sensitive strategies, recommending leadership development, mental health training, recognition systems, and proactive workload management to improve staff wellbeing. It also identifies directions for future research, including longitudinal validation, exploration of role-specific stressors, and cross-cultural comparisons to assess the influence of cultural and institutional factors on burnout development. This conceptual model offers an evidence-informed foundation for universities to design strategic interventions that move beyond reactive responses and towards a systematic, sustainable approach to protecting employee mental health and enhancing institutional effectiveness.